THE APPLICATION OF HEALING ARCHITECTURE CONCEPT IN TYPE B REGIONAL HOSPITAL, KARANGANYAR REGENCY, CENTRAL JAVA - Mushadik Mushadik; Rita Laksmitasari Rahayu (Universitas Indraprasta PGRI, 2023)
As a health service, hospitals have benefits for the community by providing medical facilities and medical support facilities. In several Regional General Hospitals in Indonesia, the patient's condition experiences various psychological conditions such as experiencing anxiety and notifications related to the patient's medical diagnosis. This results in feelings of sadness, decreased enthusiasm, and experiencing difficulty sleeping which has a negative impact on physical recovery. Healing architecture - Evidence-based design as one of the architectural design concepts that plays a role in the patient's healing process that is creative and innovative so that it is beneficial for the benefit of patients and staff. The biophilic design method is used as an approach to produce a design for a hospital in Karanganyar with a healing architecture concept. The 2 principles of healing architecture approach used are landscape and nature & outdoors. The method of designing biophilic designs is in accordance with the principles of healing architecture where the principles of design patterns are able to connect between humans and nature. The novelty of this design is that the RSUD in Karanganyar Regency has not been optimal in applying the concept of healing architecture